Rare primary pleomorphic rhabdomyosarcoma of the thyroid gland with lung and adrenal metastases: a case report and literature review - Altabbouche, Rami; Musiał, Jacek; Jałocha-Kaczka, Anna; Dziki, Łukasz; Maryńczak, Kasper; Kaczka, Krzysztof (Frontiers in Oncology, 2026)
Primary thyroid pleomorphic rhabdomyosarcoma (PRMS) is an extremely rare and aggressive neoplasm, with only five cases reported in the literature to date. We present the sixth reported case of primary thyroid PRMS and the first case demonstrating distal metastases to the lungs and left adrenal gland in a 71-year-old female. The patient underwent total thyroidectomy with lymphadenectomy, with histopathological evaluation confirming PRMS and demonstrating a highly aggressive biological behavior. The immunophenotypic profile showed strong immunopositivity for skeletal muscle markers, including desmin and vimentin. Further computerized tomography imaging identified a metastasized lesion in the left adrenal gland and a diffuse lung nodular dissemination. The patient received a personalized treatment plan which combined both systemic chemotherapy and radiotherapy. After four cycles of chemotherapy, the patient achieved partial regression of metastatic lesions. The highly aggressive nature of PRMS emphasizes the importance of having individualized and multidisciplinary treatment approaches to such rare cases.